Quality of Narcotics Prevention, Eradication, Abuse, and Illicit Circulation Services (P4GN) at BNN Gorontalo Province in Drug Addict Rehabilitation Patients - Tessy Nursanty Podungge; Asna Aneta; Rusli Isa (International Journal of Education, Vocational and Social Science, 2025)
Tessy Nursanty Podungge. NIM 711524024. "Quality of Narcotics Prevention, Eradication, Abuse, and Illicit Circulation Services (P4GN) at BNN Gorontalo Province in Drug Addict Rehabilitation Patients". Supervisor I Prof. Dr. Asna Aneta, M.Si., Supervisor II Dr. Drs. Rusli Isa, M.Si.The study aims to find out and analyze the quality of narcotics prevention, eradication, abuse, and illicit circulation (P4GN) services in BNN Gorontalo Province in drug addict rehabilitation patients. The research approach used is a qualitative method with descriptive research methods and research procedures carried out by observation and interviews with informants. The data analysis technique used was the interactive analysis of the Miles and Huberman models. The results of the study show that the quality of P4GN services at BNN Gorontalo Province for drug addict rehabilitation patients shows a fairly systematic and structured implementation, especially in the dimensions of medical, non-medical, and social rehabilitation services. Each stage of rehabilitation, from assessment, detoxification, stabilization, to re-entry and after care, is carried out with a multidisciplinary approach that prioritizes team coordination, family involvement, and community involvement. However, budget constraints and the suboptimal sustainability of post-rehabilitation economic empowerment programs are challenges that can affect patient recovery resilience. However, the existence of service practices based on empathy, responsiveness, and quality assurance through periodic evaluation and social support shows that BNN Gorontalo Province strives to maintain the quality of service professionally. This reflects that drug rehabilitation services in the institution have moved towards sustainable recovery and are oriented towards the social reintegration of former addicts in a sustainable manner.